2018
DOI: 10.1007/s40620-018-0504-4
|View full text |Cite
|
Sign up to set email alerts
|

Women and acute kidney injury in myocardial infarction

Abstract: AKI occurs more often in women than men with MI undergoing PCI. Female gender independently predicted AKI in our analysis. A high CV/GFR denotes a group of patients who are at higher risk of AKI after PCI. CV/GFR was significantly higher in women, which may help to explain their worse outcome as regards AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This condition is mostly related to the enhancement of coronary shear stress, which is mostly caused by high physical load or emotional stress in young people. Domestic studies have shown that with the increase of age, the number of coronary artery lesions in patients with acute coronary syndrome will also increase [18]. However, there is still no uniform conclusion on whether there is a difference in the number of coronary lesions between genders.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is mostly related to the enhancement of coronary shear stress, which is mostly caused by high physical load or emotional stress in young people. Domestic studies have shown that with the increase of age, the number of coronary artery lesions in patients with acute coronary syndrome will also increase [18]. However, there is still no uniform conclusion on whether there is a difference in the number of coronary lesions between genders.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 55.6% of the high creatinine group have eGFR between 15 and 30 mL/min/1.73 m 2 . It has been found that a high mortality rate among COVID-19 patients and a higher probability of developing AKI were associated with lower GFR (51-85 mL/min/1.73 m 2 ) [20] [21] . Concerning electrolytes levels, our results demonstrated that serum sodium concentration was significantly lower in COVID-19 patients and even lower in the severe COVID-19 positive group compared to the non-severe group.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have consistently shown a protective effect of female on the development of AKI after ischemia-reperfusion injury [6,25,26]. Contrary to these experimental observations, the direction of sexual dimorphism has been reported to be controversial in AKI in human [23,27]. Some studies demonstrated that female was associated with improved survival in critically ill patients with septic acute kidney injury [28].…”
Section: Relationship Of Findings To Other Relevant Studiesmentioning
confidence: 99%